Breeze, Andrew. 2023. The Historical Arthur and the “Gawain” Poet: Studies on Arthurian and Other Traditions. London: Lexington Books. Pp. x + 153. ISBN 978166692956. - Warner, Lawrence (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Breeze, Andrew. 2023. The Historical Arthur and the “Gawain” Poet: Studies on Arthurian and Other Traditions. London: Lexington Books. Pp. x + 153. ISBN 978166692956.